Shifts in functional trait composition across successional stages and how they affect aboveground carbon stocks in secondary subtropical forests - Jean M. Freitag Kramer; Tanise Sausen; Kauane Maiara Bordin; Elivane Salete Capellesso; Carolina Prauchner; Katia J. Zanini; Gabriel Wiater; Cimélio Bayer; Sandra Cristina Müller (Forest Ecology and Management, 2026)

Diverse prokaryotic strategies associated with soil organic matter priming - M. Waibel; E. Paterson; T.E. Freitag; F. Abram; P.E. Hedley; J. Morris; L.J. Robinson; A. Sim; B. Thornton; F.P. Brennan (Applied Soil Ecology, 2026)

Effects of Deforestation and Fragmentation on Tree Beta Diversity and Endemism Across Landscapes in the Atlantic Forest Biodiversity Hotspot - Jean M. Freitag Kramer; Victor P. Zwiener; Mateus Camana; Renato A. F. de Lima; Sandra Cristina Müller (Global Change Biology, 2026)
Biodiversity is highly heterogeneous across space, shaped by factors such as climate, geographical distance, and human activities. However, as we enter the Anthropocene, the impacts of habitat loss and fragmentation on biodiversity are becoming increasingly severe and insufficiently disentangled. Here we assess how habitat amount, habitat fragmentation, regional climate, and geographical distance influence beta diversity and endemism levels in tree communities across 95 landscapes in the Brazilian Atlantic Forest. We generated landscapes of 100 km 2 around forest inventory data extracted from the Neotropical Tree Communities database (TreeCo). Each landscape was characterized in terms of habitat amount, fragmentation (number of patches, mean patch size, and mean distance to the nearest neighbor), mean spatial distance (geographical distance among forest inventories), and climate across the region. The landscape variables (habitat amount and fragmentation) and the mean spatial distance were stronger predictors of beta diversity and endemism level when compared to regional climate. Beta diversity declined with increasing fragmentation, suggesting biotic homogenization in highly fragmented landscapes. On the other hand, spatial distance promoted increases in beta diversity, with more dissimilar communities as the distance increased. Moreover, endemism increased with habitat amount, with higher endemism levels in landscapes with more habitat. We highlight that our study contributes to the ongoing debate on the effects of fragmentation on biodiversity, reporting negative effects of habitat fragmentation on beta diversity within landscapes across the entire Atlantic Forest. Our findings successfully separate the effects of habitat fragmentation, habitat amount, and spatial distance on biodiversity, providing a better understanding of the processes that determine biodiversity change at the landscape scale. We advocate for conservation strategies that simultaneously protect both large and smaller habitat patches to sustain tree beta diversity and endemism across human‐modified landscapes.

The landscape of agroforestry in Brazil: a synthesis of research trends, implementation patterns, and policy implications - João Victor Martinelli; Jean M. Freitag Kramer; Luana Meister; Nyamien Yahaut Sebastien; Victor Pereira Zwiener (Agroforestry Systems, 2026)
Agroforestry systems (AFSs) are often considered a means to reconcile agricultural production with biodiversity conservation, yet the alignment between scientific research and practice remains poorly understood. In Brazil, a country with widespread AFS adoption, we conducted a systematic review of 631 publications (1982–2019) and integrated them with national Agricultural Census data to map the landscape of AFS research and implementation. Our analysis shows that while scientific output has accelerated, research efforts are geographically concentrated in the Atlantic Forest and Amazon biomes, leaving other major ecosystems like the Cerrado and Caatinga under-represented. A marked discrepancy was observed in the Northeast region, which hosts two-thirds of Brazil's AFS establishments but receives disproportionately low research attention. While simple, production-oriented AFSs were more frequently studied, biodiverse systems, particularly those with very high species richness, showed a clear association with family farming and traditional knowledge. Furthermore, regression models indicated that AFS prevalence is negatively associated with market-oriented production (commercialization), a finding consistent with their role in food sovereignty. These results point to persistent regional imbalances in the research agenda and suggest the need to strengthen knowledge production in underrepresented areas to better reflect the range of AFS practices in the country.

Progress in understanding fission product remobilization and hydrogen risk in water-cooled reactors: OECD/NEA THAI-3 project - S. Gupta; M. Freitag; E. Schmidt; M. Colombet; B. von Laufenberg; G. Langrock; F. Funke (Annals of Nuclear Energy, 2025)

Impact of land-use intensity, productivity, and aboveground richness on seed rain in temperate grasslands - Y.P. Klinger; S. Kunze; N. Hölzel; M. Freitag; V.H. Klaus; T. Kleinebecker; D. Prati; L. Neuenkamp (Agriculture, Ecosystems & Environment, 2025)

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

An assessment and characterization of pharmaceuticals and personal care products (PPCPs) within the Great Lakes Basin: Mussel Watch Program (2013–2018) - Edwards M. A.; Kimbrough K.; Fuller N.; Davenport E.; Rider M.; Freitag A.; Regan S.; Leight A; K.; Burkart H.; Jacob A.; Johnson E. (Environmental Monitoring and Assessment, 2024)
Defining the environmental occurrence and distribution of chemicals of emerging concern (CECs), including pharmaceuticals and personal care products (PPCPs) in coastal aquatic systems, is often difficult and complex. In this study, 70 compounds representing several classes of pharmaceuticals, including antibiotics, anti-inflammatories, insect repellant, antibacterial, antidepressants, chemotherapy drugs, and X-ray contrast media compounds, were found in dreissenid mussel (zebra/quagga; Dreissena spp.) tissue samples. Overall concentration and detection frequencies varied significantly among sampling locations, site land-use categories, and sites sampled proximate and downstream of point source discharge. Verapamil, triclocarban, etoposide, citalopram, diphenhydramine, sertraline, amitriptyline, and DEET (N,N-diethyl-meta-toluamide) comprised the most ubiquitous PPCPs (> 50%) detected in dreissenid mussels. Among those compounds quantified in mussel tissue, sertraline, metformin, methylprednisolone, hydrocortisone, 1,7-dimethylxanthine, theophylline, zidovudine, prednisone, clonidine, 2-hydroxy-ibuprofen, iopamidol, and melphalan were detected at concentrations up to 475 ng/g (wet weight). Antihypertensives, antibiotics, and antidepressants accounted for the majority of the compounds quantified in mussel tissue. The results showed that PPCPs quantified in dreissenid mussels are occurring as complex mixtures, with 4 to 28 compounds detected at one or more sampling locations. The magnitude and composition of PPCPs detected were highest for sites not influenced by either WWTP or CSO discharge (i.e., non-WWTPs), strongly supporting non-point sources as important drivers and pathways for PPCPs detected in this study. As these compounds are detected at inshore and offshore locations, the findings of this study indicate that their persistence and potential risks are largely unknown, thus warranting further assessment and prioritization of these emerging contaminants in the Great Lakes Basin. Graphical Abstract

Hemispheric-scale heavy metal pollution from South American and Australian mining and metallurgy during the Common Era - Joseph R. McConnell; Nathan J. Chellman; Sophia M. Wensman; Andreas Plach; Charles Stanish; Pamela A. Santibáñez; Sandra O. Brugger; Sabine Eckhardt; Johannes Freitag; Sepp Kipfstuhl; Andreas Stohl (Science of The Total Environment, 2024)

A matter of scale: Local biotic differentiation and potential regional homogenization of understory plant communities in a highly fragmented tropical landscape - Jean M. Freitag Kramer; Jhéssica L. Bald; Jaqueline de Lima Pessato; Fabiane Maziero Kupas; Carina Kozera; Victor P. Zwiener (Acta Oecologica, 2023)

Biotic homogenization and differentiation of plant communities in tropical and subtropical forests - Jean M. Freitag Kramer; Victor P. Zwiener; Sandra Cristina Müller (Conservation Biology, 2023)
Anthropogenic impacts on biodiversity can lead to biotic homogenization (BH) and biotic differentiation (BD). BH is a process of increasing similarity in community composition (including taxonomic, functional, and phylogenetic components), whereas BD is a process of decreasing similarity over space and time. Here, we conducted a systematic review of BH and BD in plant communities in tropical and subtropical forests to identify trends and knowledge gaps. Our bibliometric search in the Web of Science returned 1989 papers, of which 151 matched our criteria and were included in the analysis. The Neotropical region had the largest number of articles, and Brazil was the most represented country with 92 studies. Regarding the type of change, homogenization was more frequent than differentiation (noted in 69.6% of publications). The taxonomic diversity component was measured more often than functional and phylogenetic diversity components. Most studies (75.6%) assessed homogenization and differentiation based on a single observation in time; as opposed to few studies that monitored plant community over multiple years. Forest fragmentation was cited as the main determinant of homogenization and differentiation processes (57.2% of articles). Our results highlight the importance of evaluating community composition over time and more than taxonomic components (i.e., functional and phylogenetic) to advance understanding of homogenization and differentiation. Both processes were scale dependent and not mutually exclusive. As such, future research should consider differentiation as a potential transition phase to homogenization and that potential differences in both processes may depend on the spatial and temporal scale adopted. Understanding the complexity and causes of homogenization and differentiation is essential for biodiversity conservation in a world increasingly affected by anthropogenic disturbances.

Microalgae Consortia for Post-treating Effluent of Anaerobic Digestion of Cattle Waste and Evaluation of Biochemical Composition of Biomass - Francisco G. Magro; João F. Freitag; André Bergoli; Jorge Alberto Vieira Costa; Luciane M. Colla (BioEnergy Research, 2022)

Sex matters: association between callous-unemotional traits and uncinate fasciculus microstructure in youths with conduct disorder - Thomas Villemonteix; Jack C. Rogers; Ophélie Courbet; Karen Gonzalez-Madruga; Gregor Kohls; Nora M. Raschle; Christina Stadler; Kerstin Konrad; Christine M. Freitag; Graeme Fairchild; Stéphane A. De Brito (Brain Imaging and Behavior, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Microalgae consortia cultivation using effluents for bioproduct manufacture - F. G. Magro; J. F. Freitag; A. Bergoli; V. A. F. Cavanhi; L. M. Colla (Reviews in Environmental Science and Bio/Technology, 2021)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Sterols in red macroalgae from antarctica: extraction and quantification by Gas Chromatography–Mass spectrometry - Ivandra Ignês de Santi; Bruna Silveira Pacheco; Dalila Venzke; Rogério Antonio Freitag; Leandro Silva de Almeida; Pio Colepicolo; Mutue Toyota Fujii; Daiane Dias; Claudio M. P. Pereira (Polar Biology, 2021)

Assessing the State of Coupled Social-Ecological Modeling in Support of Ecosystem Based Fisheries Management in the United States - Stephen Kasperski; Geret S. DePiper; Alan C. Haynie; Suzana Blake; Lisa L. Colburn; Amy Freitag; Michael Jepson; Mandy Karnauskas; Kirsten M. Leong; Douglas Lipton; Michelle Masi; Cameron Speir; et al. (Frontiers in Marine Science, 2021)
There has been a proliferation of coupled social-ecological systems (SES) models created and published in recent years. However, the degree of coupling between natural and social systems varies widely across the different coupled models and is often a function of the disciplinary background of the team conducting the research. This manuscript examines models developed for and used by NOAA Fisheries in support of Ecosystem Based Fisheries Management (EBFM) in the United States. It provides resource managers and interdisciplinary scientists insights on the strengths and weaknesses of the most commonly used SES models: end-to-end models, conceptual models, bioeconomic models, management strategy evaluations (MSEs), fisher behavior models, integrated social vulnerability models, and regional economic impact models. These model types are not unique to the literature, but allow us to differentiate between one-way coupled models – where outputs from one model are inputs into a second model of another discipline with no feedback to the first model, and two-way coupled models – where there are linkages between the natural and social system models. For a model to provide useful strategic or tactical advice, it should only be coupled to the degree necessary to understand the important dynamics/responses of the system and to create management-relevant performance metrics or potential risks from an (in)action. However, one key finding is to not wait to integrate! This paper highlights the importance of “when” the coupling happens, as timing affects the ability to fully address management questions and multi-sectoral usage conflicts that consider the full SES for EBFM or ecosystem based management (EBM) more generally.

Significance of Beta-Band Oscillations in Autism Spectrum Disorders During Motor Response Inhibition Tasks: A MEG Study - Vera Moliadze; Alla Brodski-Guerniero; Magdalena Schuetz; Julia Siemann; Ekaterina Lyzhko; Sabine Schlitt; Janina Kitzerow; Anne Langer; Jochen Kaiser; Marcus J. Naumer; Michael Wibral; Jason Chan; et al. (Brain Topography, 2020)
In Autism Spectrum Disorders (ASD), impaired response inhibition and lack of adaptation are hypothesized to underlie core ASD symptoms, such as social communication and repetitive, stereotyped behavior. Thus, the aim of the present study was to compare neural correlates of inhibition, post-error adaptation, and reaction time variability in ASD and neuro-typical control (NTC) participants by investigating possible differences in error-related changes of oscillatory MEG activity. Twelve male NTC (mean age 20.3 ± 3.7) and fourteen male patients with ASD (mean age 17.8 ± 2.9) were included in the analysis. Subjects with ASD showed increased error-related reaction time variability. MEG analysis revealed decreased beta power in the ASD group in comparison to the NTC group over the centro-parietal channels in both, the pre-stimulus and post-response interval. In the ASD group, mean centro-parietal beta power negatively correlated with dimensional autism symptoms. In both groups, false alarms were followed by an early increase in temporo-frontal theta to alpha power; and by a later decrease in alpha to beta power at central and posterior sensors. Single trial correlations were additionally studied in the ASD group, who showed a positive correlation of pre-stimulus beta power with post-response theta, alpha, and beta power, particularly after hit trials. On a broader scale, the results deliver important insights into top-down control deficits that may relate to core symptoms observed in ASD.

Knock‐down of the methyltransferase Kmt6 relieves H3K27me3 and results in induction of cryptic and otherwise silent secondary metabolite gene clusters in Fusarium fujikuroi - Lena Studt; Sarah M. Rösler; Immo Burkhardt; Birgit Arndt; Michael Freitag; Hans‐Ulrich Humpf; Jeroen S. Dickschat; Bettina Tudzynski (Environmental Microbiology, 2016)
Summary Filamentous fungi produce a vast array of secondary metabolites (SMs) and some play a role in agriculture or pharmacology. Sequencing of the rice pathogen Fusarium fujikuroi revealed the presence of far more SM‐encoding genes than known products. SM production is energy‐consuming and thus tightly regulated, leaving the majority of SM gene clusters silent under laboratory conditions. One important regulatory layer in SM biosynthesis involves histone modifications that render the underlying genes either silent or poised for transcription. Here, we show that the majority of the putative SM gene clusters in F. fujikuroi are located within facultative heterochromatin marked by trimethylated lysine 27 on histone 3 (H3K27me3). Kmt6, the methyltransferase responsible for establishing this histone mark, appears to be essential in this fungus, and knock‐down of Kmt6 in the KMT6 kd strain shows a drastic phenotype affecting fungal growth and development. Transcription of four so far cryptic and otherwise silent putative SM gene clusters was induced in the KMT6 kd strain, in which decreased expression of KMT6 is accompanied by reduced H3K27me3 levels at the respective gene loci and accumulation of novel metabolites. One of the four putative SM gene clusters, named STC5, was analysed in more detail thereby revealing a novel sesquiterpene.

Does the use of small aids during patient handling activities lead to a decreased occurrence of musculoskeletal complaints and diseases? A systematic review - A. Freiberg; U. Euler; M. Girbig; A. Nienhaus; S. Freitag; A. Seidler (International Archives of Occupational and Environmental Health, 2016)

A Candidate Gene Association Study Identifies DAPL1 as a Female-Specific Susceptibility Locus for Age-Related Macular Degeneration (AMD) - Felix Grassmann; Ulrike Friedrich; Sascha Fauser; Tina Schick; Andrea Milenkovic; Heidi L. Schulz; Claudia N. von Strachwitz; Thomas Bettecken; Peter Lichtner; Thomas Meitinger; Nicole Arend; Armin Wolf; et al. (NeuroMolecular Medicine, 2015)

Common variants in genes of the postsynaptic FMRP signalling pathway are risk factors for autism spectrum disorders - Regina Waltes; Eftichia Duketis; Michael Knapp; Richard J. L. Anney; Guillaume Huguet; Sabine Schlitt; Tomasz A. Jarczok; Michael Sachse; Laura M. Kämpfer; Tina Kleinböck; Fritz Poustka; Sven Bölte; et al. (Human Genetics, 2014)

Dendritic cells regulate angiogenesis associated with liver fibrogenesis - Sandra M. Blois; Flavia Piccioni; Nancy Freitag; Irene Tirado-González; Petra Moschansky; Rodrigo Lloyd; Karin Hensel-Wiegel; Matthias Rose; Mariana G. Garcia; Laura D. Alaniz; Guillermo Mazzolini (Angiogenesis, 2014)

CXCR4+ Dendritic cells promote angiogenesis during embryo implantation in mice - Gabriela Barrientos; Irene Tirado-González; Nancy Freitag; Peter Kobelt; Petra Moschansky; Burghard F. Klapp; Victor L. J. L. Thijssen; Sandra M. Blois (Angiogenesis, 2013)

Parameters determining the efficacy of adoptive CD8 T-cell therapy of cytomegalovirus infection - Stefan Ebert; Jürgen Podlech; Dorothea Gillert-Marien; Kerstin M. Gergely; Julia K. Büttner; Annette Fink; Kirsten Freitag; Doris Thomas; Matthias J. Reddehase; Rafaela Holtappels (Medical Microbiology and Immunology, 2012)

Centromeres of filamentous fungi - Kristina M. Smith; Jonathan M. Galazka; Pallavi A. Phatale; Lanelle R. Connolly; Michael Freitag (Chromosome Research, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Protection of the right ventricle from ischemia and reperfusion by preceding hypoxia - Daniela Wasserfuhr; Sürreya M. Cetin; Jun Yang; Patricia Freitag; Stilla Frede; Heinz Jakob; Parwis Massoudy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Association of gene-linked SSR markers to seed glucosinolate content in oilseed rape (Brassica napus ssp. napus) - M. Hasan; W. Friedt; J. Pons-Kühnemann; N. M. Freitag; K. Link; R. J. Snowdon (Theoretical and Applied Genetics, 2008)

Screening zum Antibiotika-Transfer aus dem Boden in Getreide in Regionen Nordrhein-Westfalens mit großen Viehbeständen - M. Freitag; D. H. Yolcu; H. Hayen; T. Betsche; Manfred Grote (Journal of Consumer Protection and Food Safety, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effect of eye movements on the magnitude of functional magnetic resonance imaging responses in extrastriate cortex during visual motion perception - P. Freitag; M. W. Greenlee; T. Lacina; K. Scheffler; E. W. Radü (Experimental Brain Research, 1998)